La consignación voluntaria de alimentos y su violación a los derechos de niños, niñas, y adolescentes. - Sánchez Pastuña, Edwin Raúl (2014)
Chapter I: The provision applies only to obligations to give , and implies that , if the creditor refuses to receive the proper thing , it is put at the disposal of the judicial authority , in accordance with a procedure established by the law itself ; the obligation to supply is a declarative , universal, abstract moral law only concrete, with the presentation of food demand. Chapter II: The theoretical framework I made a historical , doctrinal, legal, jurisprudence, law and comparative analysis of the research topic to formulate hypotheses to guide field research. Chapter III: The methodology used is described, Historic, Dialectical, Comparative , Hermeneutic and Analytic. Chapter IV: Analysis and interpretation of results in relation to the research hypothesis. Chapter V: The findings , led us to the voluntary provision of food is not regulated in the Code of Childhood and Adolescence, and recommendations , is that drinking regulate voluntary provision in the Code for Children and Adolescents. Chapter VI: The proposal in which the preamble is done which is necessary to reform the Reform Act Title V, Book II of the Code of Childhood and Adolescence develops, adding art. after art. unnumbered